Analysis of the Dilemma of Overseas Cross-cultural Communication of Chinese Animation Movies and the Strategy of Cross-cultural Communication in the New Media Environment: “Nezha: Birth of Demon” as An Example: 中国动画电影海外跨文化传播困境与新媒体环境下跨文化传播策略探析 ——以《哪吒之魔童降世》为例 - Yue WANG (Mandarinable: Journal of Chinese Studies, 2022)
In the 21st century, modern media technology allows cultural products to circulate throughout the world. Movies have become an important carrier of cultural exchange and dissemination. Animated movies become a breakthrough in the cross-cultural dissemination of Chinese culture. This article takes the Chinese animation movie "Nezha: Birth of the Demon Child" as an example. From the perspective of cross-cultural communication and analysis of the innovation of "Nezha: Birth of the Demon Child ", this movie inherited China's fine traditional values and is based on traditional myths and stories integrated with contemporary Chinese values, presenting the new connotation of Chinese traditional values. Aiming at the difficulties encountered in the overseas cross-cultural communication of " Nezha: Birth of the Demon Child ", this article combines the new media environment to analyze the cross-cultural communication strategies of Chinese animation movies that are represented by " Nezha: Birth of the Demon Child ".